Medieval pottery from north Lincolnshire - Hayfield, Colin (1982)
This thesis establishes and defines, for the first time, the forms and fabric types of the medieval ceramics which have been found in North Lincolnshire. The pottery from the unstratified assemblages has been catalogued in Chapter 2 and that from the stratified assemblages in Chapter 3. As an intensive regional study, there have been opportunities to use this catalogued information, along with a study of the distributional evidence, to comment on some of the wider aspects of pottery study.